2019
DOI: 10.6007/ijarbss/v9-i9/6407
|View full text |Cite
|
Sign up to set email alerts
|

Business Strategy of Small and Medium-Sized Enterprise Construction Companies in Adopting Industrialised Building System in Malaysia

Abstract: This exploratory study outlines the business strategy that are being applied by small and medium-size enterprises (SME) construction companies in adopting Industrialised Building System (IBS) in Malaysia. Case study was employed as the research method in order to achieve the research objective as it can be used to explore and give further understanding of the research issues. Cross-case synthesis and pattern matching technique were applied for the analysis of the case study. Through the study, it was found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Our selection of these two cases was strategic because they are what Flyvbjerg (2006) refers to as exception cases. They carve out space for interrogating, or at least nuancing, empirical work that argues that SMEs face constraints in collaboration (Hoffman and Schlosser, 2001; Hagedoorn and Schaknraad, 1994) and that SMEs find OSM challenging (Mohamed, 2018). Our study does not set out to provide quantifiable propositions that will suit “all” SMEs, but to provide detailed narratives and models with key elements that are nevertheless transferable to other domains (Gioia et al , 2012), under interpretivism's tempered notion of generalisability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our selection of these two cases was strategic because they are what Flyvbjerg (2006) refers to as exception cases. They carve out space for interrogating, or at least nuancing, empirical work that argues that SMEs face constraints in collaboration (Hoffman and Schlosser, 2001; Hagedoorn and Schaknraad, 1994) and that SMEs find OSM challenging (Mohamed, 2018). Our study does not set out to provide quantifiable propositions that will suit “all” SMEs, but to provide detailed narratives and models with key elements that are nevertheless transferable to other domains (Gioia et al , 2012), under interpretivism's tempered notion of generalisability.…”
Section: Methodsmentioning
confidence: 99%
“…Empirical work suggests that SMEs struggle with both OSM and collaboration. Research shows that SMEs struggle to adopt OSM due to a number of factors, including lack of knowledge and lack of financial resources (Mohamed, 2018). These are issues that could be addressed by inter-organisational alliances; however, empirical research also shows that that small firms have less propensity to form collaborations and alliances than large firms, which have higher strategic partnering rates (Hagedoorn and Schakenraad, 1994; Hoffman and Schlosser, 2001).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In 2008, all government projects were made compulsory to use IBS where a minimum of 70 IBS score must be achieved for projects worth RM10 million and above as indicated in the Treasury Circular SPP 07/2008 and construction players are encouraged to use IBS for private projects where contractors who have achieved 50 IBS score for residential are exempted from the Malaysian construction levy (Hamid et al 2008). Even though the initiative of promoting the adoption of IBS in the construction industry has been long implemented the participation of contractors in IBS business is still low especially among the Small and Medium-sized (SME) contractors (CIDB, 2015;Mohamed et al, 2018). The main reason for the low participation is due to the fact that many contractors are unlikely to accept the IBS construction and prefer to continue to use the conventional method of construction.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Zairul (2020) found that in the Malaysian context, there is limited research on proposing ground-breaking business models for IBS. In order to survive and sustain their business in the construction industry SME contractors is suggested to become IBS contractors and adopt IBS in their construction business (CIDB, 2015;Mohamed et al, 2019;Theong et al, 2018). With the move to industrialize the construction sector, SME contractors will have to establish more innovative business models and plans for turnover growth (Goh & Loosemore, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation